2006
DOI: 10.1523/jneurosci.2552-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

NR3A Modulates the Outer Vestibule of the “NMDA” Receptor Channel

Abstract: Classical NMDA receptors (NMDARs), activated by glycine and glutamate, are heteromultimers comprised of NR1 and NR2 subunits. Coexpression of the novel NR3 family of NMDAR subunits decreases the magnitude of NR1/NR2 receptor-mediated currents or forms glycine-activated channels with the NR1 subunit alone. The second (M2) and third (M3) membrane segments of NR1 and NR2 subunits of classical NMDARs form the core of the channel permeation pathway. Structural information regarding NR1/NR3 channels remains unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
2
38
1
Order By: Relevance
“…This mechanism could allow NR1 substitutions to alter the activation equilibrium of the receptor without rendering it constitutively active. Interestingly, recent work with the inhibitory NR3 subunit has indicated that its M3 domain is relatively rigid and does not undergo activationdependent rearrangement, providing a possible explanation for its "dominant-negative" effect (Wada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism could allow NR1 substitutions to alter the activation equilibrium of the receptor without rendering it constitutively active. Interestingly, recent work with the inhibitory NR3 subunit has indicated that its M3 domain is relatively rigid and does not undergo activationdependent rearrangement, providing a possible explanation for its "dominant-negative" effect (Wada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence for this idea was provided by Wada et al (2006), who showed that cysteine-substitutions in the M3 segment of GluN3A were modified by extracellular cysteine-reactive reagents and suggested that some residues lining the pore may differ from GluN1 and GluN2 subunits. Nevertheless, molecular mechanisms regulating conductance and permeability in GluN3-containing receptors are poorly understood.…”
Section: B Mechanisms Of Ion Permeationmentioning
confidence: 95%
“…This suggests that there is a direct role, in addition to the hypothesized modulatory role, of NR3 subunit in NR1/NR3 receptor activation that is supported by higher affinity of glycine for the NR3A S1S2 domain (Yao and Mayer, 2006;Awobuluyi et al, 2007). Using substituted cysteine accessibility method, Wada et al (2006) showed that the N-site residue of NR1 but not NR3 subunits forms the tip of the channel pore loop. The M3 segments of both NR1 and NR3A seemed to form a narrow constriction in the outer vestibule of the channel, thus preventing the influx of sulfhydryl-specific agents (2-aminoethyl methanethiosulfonate hydrobromide and methanethiosulfonate-ethyltrimethlammonium) applied externally (Wada et al, 2006).…”
Section: Nr1/nr3 Receptors Expressed In Oocytesmentioning
confidence: 96%
“…In oocytes, NR1/NR3 receptors exhibit novel pharmacological and functional properties Sucher et al, 1995;Wada et al, 2006;Awobuluyi et al, 2007;Madry et al, 2007). Early attempts to elicit agonist-activated currents by glutamate or NMDA on NR1/NR3A receptors expressed in Xenopus laevis oocytes generated either no robust currents (Sucher et al, 1995) or diminutive currents (Ͻ20 nA) .…”
Section: Nr1/nr3 Receptors Expressed In Oocytesmentioning
confidence: 99%
See 1 more Smart Citation